Efficacy Prediction of Four Pharmaceutical Formulations for Intramammary Administration Containing Aloe vera (L.) Burm. f. Combined With Ceftiofur or Cloxacillin in Lactating Cows as an Alternative Therapy to Treat Mastitis Caused by Staphylococcus aureus - Forno-Bell, Natalia; Munoz, Marcos A.; Chacón, Oscar; Pachá, Paulina; Iragüen, Daniela; Cornejo, Javiera; San Martín, Betty (Frontiers in Veterinary Science, 2021)
Synergy or additive effect between Aloe vera (L.) Burm. f. and beta-lactam antibiotics has been reported against Staphylococcus aureus, one of the most important etiological agents of cow mastitis. The goal of the present study was to predict the efficacy of intramammary formulations containing Aloe vera gel extract in combination with cloxacillin or ceftiofur at low concentrations in lactating cows as an alternative therapy. Each quarter of 20 healthy Holstein Friesian lactating cows were treated with a single dose of one of the following formulations, corresponding to one of these treatment groups: A1, A2, A3, and A4. A1 and A2 contained cloxacillin at 0.25 and 0.5 mg/mL, whereas A3 and A4 contained ceftiofur 0.25 and 0.5 mg/mL, respectively. In addition, all formulations contained 600 mg/mL of an alcoholic extract of Aloe vera. Milk samples were taken at predefined time points. Antibiotics and aloin (active compound of Aloe vera) concentrations were assessed by LC/MS-MS. Pharmacokinetic profiles were obtained and the efficacy index, the fraction of dosing interval in which the antimicrobial concentration remains above the MIC (T > MIC) for each formulation was calculated considering MIC values against S. aureus ATCC 29213 as obtained for the combination Aloe vera + antibiotic and aloin concentration in the extract. Mammary gland safety assessment was performed for each combination. Values of the main efficacy index for this study, T > MIC (h) for Aloe vera were 23.29, 10.50, 27.50, and 13.89, while for cloxacillin or ceftiofur were 19.20, 10.9, 19.74, and 15.63, for A1, A2, A3, and A4, respectively. Only A1 and A3 reached aloin and antibiotic recommended values as predictors of clinical efficacy for cloxacillin, ceftiofur and aloin (50%, 70%, and 60%, respectively), assuming a dose interval of 24 h. The efficacy index values obtained suggest that A1 and A3 might be an effective therapy to treat bovine mastitis caused by S. aureus after a single dose. Nevertheless, further trials in S. aureus mastitis clinical cases are mandatory to confirm the efficacy of Aloe vera formulations.